MJSSM Editors among Top Scientists Cited Worldwide in Stanford List - Bojan Masanovic (Montenegrin Journal of Sports Science and Medicine, 2022)
In ancient times, science was practiced only by the privileged, primarily because of its poor accessibility. However, the development of ICT has enabled modern man to make science much more accessible to him/ her. For that reason, today, there are many more scientists who are trying to change the world for the better with their activities. In the race for new knowledge and original discoveries, scientists want to be better than others. Different metrics are used to measure quality among scientists. Stanford University recently published an updated list of the best scientists in the world, which is considered one of the most prestigious. On a recently published list, three editors of Montenegrin Journal of Sports Science and Medicine: Yousef Saleh Khader, Sergej M. Ostojic and Stevo Popovic have been ranked among the world’s top 2% most-cited scientists in 2020 and the purpose of this editorial is to recognize and promote their scientific impact and scientific excellence.